245 Likelihood of live birth following fertility preserving treatment among reproductive-age women diagnosed with gynecologic malignancies or pre-malignancies. (April 2022) - Yu, Ruoxi; Christianson, Mindy S.; Beavis, Anna L.; Stone, Rebecca L.; Hopkins, Johns
Abstract : OBJECTIVES/GOALS: To determine the impact of fertility preserving treatment (FPT) on likelihood of live birth in a cohort of reproductive-age women (18-45 y) after diagnosis of gynecologic malignancy or pre-malignancy METHODS/STUDY POPULATION: We performed a retrospective cohort study of women ages 18-45 seen by gynecologic oncologists for newly diagnosed cervical cancer (CC), endometrial intraepithelial neoplasia (EIN) or endometrial cancer (EC), and borderline ovarian tumor (BOT) or invasive ovarian cancer (OC) at an academic center from 2015-2019, excluding women who completed childbearing. Our primary outcome was live birth after diagnosis and our exposure was FPT defined as services received by reproductive endocrinology and infertility specialists. We performed Pearsons Chi-squared and log binomial regression to assess association between live birth and FPT with adjustment for patient demographic and disease factors. RESULTS/ANTICIPATED RESULTS: Out of 220 women (median age 36 y), most were White (54% vs. 25% Black) and 37% percent were diagnosed with BOT/OC (vs. 35% EIN/EC; 28% CC). After diagnosis of disease, 19% of women (n=41) had documented FPT and 8% of women (n= 17) had a live birth. By the end of follow-up, 6% of women who did not receive FPT had a live birth (n=11/178) compared to 15% of those who did (n=6/40, p=0.12). In univariate regression, women who received FPT were 2.4 times more likely to have a live birth after disease diagnosis that those who did not receive FPT (p-value = 0.06). However, after adjusting for age at diagnosis, relationship status, disease stage and disease type, the association between FPT and live birth was less robust (RR = 1.4, p-value = 0.6). DISCUSSION/SIGNIFICANCE: In this study, a minority of women had FPT or live births. Our data suggest that FPT benefit should be considered in context of age, relationship status, and disease characteristics for reproductive-age women diagnosed with gynecologic malignancies. Given the complexity, women should be offered referral for consultation with a fertility specialist.